Thin Films Deposition Methods and Applications - Yang, Dongfang (IntechOpen, 2023)
A thin film is a layer of material ranging from fractions of a nanometer to several micrometers in thickness. Thin films have been employed in many applications to provide surfaces that possess specific optical, electronic, chemical, mechanical and thermal properties. Through ten chapters consisting of original research studies and literature reviews written by experts from the international scientific community, this book covers the deposition and application of thin films.